MABS graft copolymer resin, preparation method and transparent MABS resin composition

By controlling the mass proportion and particle size distribution of polybutadiene rubber particles in the MABS graft copolymer resin, the problem of insufficient between high transparency and impact resistance of existing transparent ABS resin is solved, and the combination of high transparency and impact resistance is achieved, and the overall performance of the resin is improved.

CN119798552AActive Publication Date: 2025-04-11WANHUA CHEM GRP CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510002834.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

The existing transparent ABS resin has a deficit between maintaining high transparency and impact resistance, resulting in its limitation in some application scenarios.

Method used

By controlling the mass proportion of large particles of polybutadiene rubber particles in the MABS graft copolymer resin, and combining the specified rubber particle size and particle size distribution index, a transparent MABS resin composition with high transparency and impact resistance was prepared.

Benefits of technology

It achieves both high transparency and impact resistance, improves the overall performance of transparent MABS resin, making it suitable for a wider range of application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005225918380000071
    Figure BDA0005225918380000071
  • Figure BDA0005225918380000081
    Figure BDA0005225918380000081
  • Figure BDA0005225918380000091
    Figure BDA0005225918380000091
Patent Text Reader

Abstract

The invention provides MABS graft copolymer resin, a preparation method and a transparent MABS resin composition. The MABS grafted copolymer resin is prepared from the following raw materials in parts by mass: 50 to 70 parts of polybutadiene rubber latex, 25 to 35 parts of alkyl acrylate monomers, 10 to 15 parts of styrene monomers and 1 to 10 parts of acrylonitrile monomers. Wherein the average particle size of the polybutadiene rubber latex is 260-300nm, the particle size distribution (PDI) is less than or equal to 0.15, the content of the MABS resin with the particle size greater than or equal to 800nm accounts for not more than 10wt%, and the transparent ABS graft copolymer resin and the transparent ABS resin composition prepared from the polybutadiene rubber latex have excellent transparency and impact resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymers, and in particular relates to an acrylonitrile-butadiene-styrene-methyl methacrylate (MABS) graft copolymer resin, a preparation method and a transparent MABS resin composition. Background Art

[0002] As consumers' requirements for quality of life continue to improve, ABS materials are gradually required to have both excellent intrinsic performance and good appearance quality in the fields of home appliances, automobiles, communication equipment and computers where ABS resin is widely used. For example, in recent years, industrial development and large product differentiation have caused great changes in product design. The transparent design of products has attracted considerable attention. Changes in design require changes in raw materials. Therefore, a large amount of research on transparent materials is actively underway.

[0003] For this reason, a variety of technologies have been developed to impart transparency to acrylonitrile-butadiene-styrene (ABS) resins by introducing alkyl acrylate or alkyl methacrylate monomers into ABS resins. Patent CN1297580C obtains acrylonitrile-butadiene-styrene copolymer transparent resins with good chemical resistance and transparency by graft copolymerization on a) conjugated diene latex; b) alkyl methacrylate or alkyl acrylate compounds; c) aromatic vinyl compounds; and d) acrylonitrile compounds and a method for preparing the same. The optical properties of the resin obtained by the method are average, and the haze value is above 2.1; Patent CN101072803B discloses a method for preparing a styrene-acrylonitrile-acrylate terpolymer transparent resin and a styrene-acrylonitrile-acrylate terpolymer transparent resin prepared by the method. The transparent resin is easy to mold due to good fluidity, can be mixed with a variety of other compounds due to good chemical resistance, and is almost not thermally faded due to good anti-fading properties, but the transparent ABS resin obtained by the method has poor impact strength and limited application scenarios.

[0004] Therefore, it is of great practical significance to study and prepare a transparent ABS resin composition having both high transparency and high impact resistance. Summary of the invention

[0005] Therefore, in view of the above problems existing in the prior art, the present invention is made. One object of the present invention is to provide a MABS graft copolymer resin and a preparation method, especially by controlling the mass proportion of large particles of polybutadiene rubber particles in the MABS graft copolymer resin, while obtaining a specified rubber particle size and particle size distribution index.

[0006] Another object of the present invention is to provide a transparent MABS resin composition, which introduces the above-mentioned MABS graft copolymer resin, thereby obtaining a transparent MABS resin composition having high transparency and impact resistance.

[0007] In order to achieve the above technical effects, the present invention adopts the following technical solutions:

[0008] According to one aspect of the present invention, there is provided a MABS graft copolymer resin, which is prepared from raw materials comprising the following components in parts by weight:

[0009] 50-70 parts of polybutadiene rubber latex,

[0010] 25-35 parts of alkyl acrylate monomer,

[0011] 10-15 parts of styrene monomer,

[0012] 1-10 parts of acrylonitrile monomer;

[0013] The average particle size of the polybutadiene rubber latex is 260-300 nm, and the particle size distribution is

[0014] (PDI)≤0.15, and the content of particles with a particle size greater than or equal to 800nm ​​is not higher than 10wt%.

[0015] Specifically, the raw material mass percentage of the MABS graft copolymer resin is as follows:

[0016] The polybutadiene rubber latex may be 50 parts by mass, 52 parts by mass, 55 parts by mass, 58 parts by mass,

[0017] 60 parts by mass, 62 parts by mass, 65 parts by mass, 68 parts by mass, 70 parts by mass, etc.,

[0018] The amount of the alkyl acrylate monomer may be 25 parts by mass, 27 parts by mass, 30 parts by mass, 32 parts by mass, 33 parts by mass, 35 parts by mass, etc.

[0019] The styrene monomer may be 10 parts by mass, 11 parts by mass, 12 parts by mass, 13 parts by mass, 14 parts by mass, 15 parts by mass, etc.

[0020] The amount of the acrylonitrile-based monomer may be 1 part by mass, 3 parts by mass, 5 parts by mass, 7 parts by mass, 9 parts by mass, 10 parts by mass, or the like.

[0021] Specifically, the MABS graft copolymer resin, wherein the average particle size of the polybutadiene rubber latex can be 260nm, 270nm, 280nm, 290nm, 300nm, etc.;

[0022] The particle size distribution (PDI) can be 0.15, 0.14, 0.13, 0.12, 0.11, 0.10,

[0023] 0.08, 0.05, 0.03, etc.

[0024] The content of particles with a diameter greater than or equal to 800 nm can be 10wt%, 9wt%, 8wt%, 7wt%,

[0025] 6wt%, 5wt%, 4wt%, 3wt%, 2wt%, 1wt%, etc.

[0026] In one embodiment of the present invention, the alkyl acrylate monomer is one or more selected from methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, decyl (meth)acrylate and lauryl (meth)acrylate.

[0027] In one embodiment of the present invention, the styrene monomer is one or more selected from styrene, α-methylstyrene, p-methylstyrene and vinyltoluene.

[0028] In one embodiment of the present invention, the acrylonitrile monomer is one or more selected from acrylonitrile, methacrylonitrile and ethacrylonitrile.

[0029] In one embodiment of the present invention, the polybutadiene rubber latex is butadiene homopolymer rubber latex.

[0030] According to another aspect of the present invention, there is provided a method for preparing the MABS graft copolymer resin, the method comprising the following steps:

[0031] S1: adding 70-110 parts by mass (preferably 80-100 parts by mass) of deionized water, 1-5 parts by mass (preferably 2-4 parts by mass) of electrolyte, 1-5 parts by mass (preferably 2-4 parts by mass) of emulsifier (1), 0.1-3 parts by mass (preferably 0.2-2 parts by mass) of molecular weight control agent (1), 60-80 parts by mass (preferably 65-75 parts by mass) of butadiene and 0.1-3 parts by mass (preferably 0.2-2 parts by mass) of initiator (1) to a reactor, starting stirring and heating the reactor to 65-85° C. (preferably 70-80° C.);

[0032] When the butadiene conversion rate reaches 20-30% (preferably 22-28%), add 10-30 parts by mass (preferably 12-20 parts by mass) of butadiene and continue the reaction;

[0033] When the butadiene conversion rate reaches 50-60% (preferably 52-58%), 10-30 parts by mass (preferably 12-20 parts by mass) of butadiene and 0.1-3 parts by mass (preferably 0.2-2 parts by mass) of initiator (2) are added and the reaction is continued;

[0034] When the butadiene conversion rate reaches 70-80% (preferably 72-78%), add 0.1-2 parts by mass (preferably 0.2-1.8 parts by mass) of emulsifier (2) and 0.1-3 parts by mass (preferably 0.2-2 parts by mass) of initiator (3) and continue the reaction;

[0035] When the butadiene conversion rate reaches ≥86% (preferably ≥88%), the reaction is terminated by cooling to obtain a polybutadiene rubber latex;

[0036] S2: 25-50 parts by mass (preferably 30-45 parts by mass) of deionized water, 25-35 parts by mass (preferably 27-33 parts by mass) of alkyl acrylate monomer, 10-15 parts by mass (preferably 11-14 parts by mass) of styrene monomer and 1-10 parts by mass (preferably 2-8 parts by mass) of acrylonitrile monomer, 0.001-0.1 parts by mass (preferably 0.002-0.08 parts by mass) of reducing agent, 0.01-1 parts by mass (preferably 0.02-0.8 parts by mass) of complexing agent, 0.01-1 parts by mass (preferably 0.02-0.8 parts by mass) of auxiliary reducing agent, 0.5-5 parts by mass (preferably 0.6-3 parts by mass) of emulsifier (3 ), 0.1-3 parts by mass (preferably 0.2-2 parts by mass) of a molecular weight control agent (2) and 0.01-0.3 parts by mass (preferably 0.02-0.29 parts by mass) of an initiator (4) are continuously added to 50-70 parts by mass (preferably 55-65 parts by mass) of the polybutadiene rubber latex prepared in step S1, so that these monomers are graft polymerized, and the continuous feeding time is 3-6 hours (preferably 3.5-5.5 hours). During the continuous feeding, the temperature is controlled at 50-65°C (preferably 55-60°C). After the feeding is completed, the temperature is raised to 65-80°C (preferably 68-75°C) and the aging is continued for 1-3 hours (preferably 1.5-2.5 hours) to obtain a MABS graft copolymer resin.

[0037] In one embodiment of the present invention, step S1 is performed under a nitrogen atmosphere.

[0038] In one embodiment of the present invention, the emulsifiers (1), (2) and (3) are one or more selected from potassium oleate, potassium rosinate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium dodecyl allyl sulfosuccinate, dipotassium C16-C18 alkenyl succinate and dioctyl sodium sulfosuccinate.

[0039] In one embodiment of the present invention, the initiators (1), (2) and (3) are one or more water-soluble initiators selected from one or more of potassium persulfate, sodium persulfate, ammonium persulfate and hydrogen peroxide.

[0040] In one embodiment of the present invention, the initiator (4) is one or more of the oil-soluble initiators, selected from one or more of diisopropylbenzene hydroperoxide, tert-hexyl hydroperoxide, diisopropylbenzene peroxide, tert-butyl isopropylbenzene peroxide, methyl ethyl ketone peroxide, methyl isobutyl ketone peroxide, cyclohexanone peroxide, isopropylbenzene hydroperoxide, tert-butyl hydroperoxide, benzoyl peroxide, lauroyl peroxide, tert-butyl perbenzoate, tert-butyl peroxy-2-ethylhexanoate and bis(4-tert-butylcyclohexyl)peroxydicarbonate.

[0041] In one embodiment of the present invention, the electrolyte is one or more of potassium carbonate, sodium carbonate, potassium bicarbonate, sodium bicarbonate, sodium phosphate, sodium pyrophosphate, potassium pyrophosphate, and sodium tripolyphosphate.

[0042] In one embodiment of the present invention, the molecular weight control agents (1) and (2) are C8-C14 alkyl mercaptans selected from one or more of tert-dodecyl mercaptan, n-dodecyl mercaptan, n-octyl mercaptan, primary octyl mercaptan, secondary octyl mercaptan and tert-octyl mercaptan.

[0043] In one embodiment of the present invention, the reducing agent is one or both of ferrous sulfate and ferrous chloride.

[0044] In one embodiment of the present invention, the complexing agent is one or more of trisodium nitrilotriacetate, disodium ethylenediaminetetraacetate, tetrasodium ethylenediaminetetraacetate, sodium pyrophosphate, and sodium hexametaphosphate.

[0045] In one embodiment of the present invention, the auxiliary reducing agent is one or more of sodium dithionite, sodium formaldehyde sulfoxylate, isoascorbic acid, glucose, and lactose.

[0046] The MABS graft copolymer resin prepared by the method of step S2 of the present invention is in the form of latex, and can be recovered as powder through treatment processes such as coagulation, dehydration and drying processes. Here, for coagulation, salts such as calcium chloride, magnesium sulfate or aluminum sulfate can be used; or acidic compounds such as sulfuric acid, nitric acid or hydrochloric acid or mixtures thereof can be used as coagulants, which can be added in a mass ratio commonly used in the art. The above-mentioned treatment processes are all conventional operating methods in the field, and the operating conditions and operating parameters used can be obtained by technicians based on the prior art. The present invention does not make specific requirements and will not be repeated here.

[0047] According to another aspect of the present invention, there is provided a transparent MABS resin composition comprising the above-mentioned MABS graft copolymer resin and methyl methacrylate-styrene-acrylonitrile (MSAN) resin;

[0048] The content of the MABS graft copolymer resin in the transparent MABS resin composition is 5-30wt%, preferably 15-25wt%, and more preferably 20-25wt%.

[0049] The MSAN resin according to the present invention is a product disclosed in the prior art, and can be a commercially available product purchased through commercial channels, or can be prepared by itself using existing processes. The present invention has no special requirements for its source.

[0050] In one embodiment of the present invention, the MSAN resin is a resin prepared by polymerizing 0-75 parts by weight of an alkyl (meth)acrylate monomer, 10-50 parts by weight of a styrene monomer, and 10-20 parts by weight of an acrylonitrile monomer.

[0051] Specifically, the polymerization reaction can be a polymerization method conventionally used in the field, such as bulk polymerization, solution polymerization, suspension polymerization, etc. The equipment used, specific operating conditions and selected operating parameters can be obtained by technicians by referring to the prior art, and the present invention has no special requirements.

[0052] Depending on its intended use, the transparent MABS resin composition may further include one or more additives selected from lubricants, antioxidants, antistatic agents, release agents and UV stabilizers. These additives are conventional additives and can be selected from conventional types in the field. For example, the lubricant can be selected from ethylene bis stearamide, polyethylene oxide wax, metal stearate and various silicone oils, and the amount of the lubricant used can be 0-5 parts by weight, preferably 0.1-2 parts by weight, based on 100 parts by weight of the transparent MABS resin composition.

[0053] The transparent MABS resin composition can be kneaded to provide a thermoplastic transparent MABS resin. More specifically, the transparent MABS resin composition is uniformly dispersed using a single screw extruder or a twin screw extruder. The dispersed composition is passed through a water bath, and cut and blown to obtain a granular thermoplastic transparent MABS resin.

[0054] According to yet another aspect of the present invention, a thermoplastic transparent MABS resin is provided, which is prepared by extruding and injection molding the transparent MABS resin composition.

[0055] Specifically, the thermoplastic transparent MABS resin of the present invention has a light transmittance of 91.0 or more and a haze value of 1.8 or less measured on a 3 mm thick sheet at room temperature according to ASTM D1003;

[0056] Izod impact strength measured at 1 / 4" according to ASTM D256 is 16 kJ / m 2 above.

[0057] Compared with the prior art, the present invention has the following beneficial effects:

[0058] The invention provides a MABS graft copolymer resin and a transparent MABS resin composition. By controlling the volume proportion of large particles of polybutadiene rubber particles in the MABS graft copolymer resin, a specified rubber particle size and a particle size distribution index are obtained at the same time, thereby obtaining a transparent MABS resin composition with high transparency and impact resistance.

[0059] Specific implementation method

[0060] In order to better understand the technical solution of the present invention, the content of the present invention is further described below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0061] Unless otherwise specified, the raw materials used in the following examples and comparative examples of the present invention are obtained from common commercial channels.

[0062] Examples 1-5

[0063] According to the types, amounts, and experimental conditions of the raw materials in Table 1, polybutadiene rubber latex (A-1 to 5) was prepared according to the following steps:

[0064] Under a nitrogen atmosphere, add 70-110 g of deionized water, 1-5 g of electrolyte, 1-5 g of emulsifier (1), 0.1-3 g of molecular weight control agent (1), 60-80 g of butadiene (A) and 0.1-3 g of initiator (1) into a reactor, start stirring and heat the reactor to a reaction temperature of 65-85° C.;

[0065] When the butadiene conversion rate (1) is 20-30%, 10-30 g of butadiene (B) is added and the reaction is continued;

[0066] When the butadiene conversion rate (2) reaches 50-60%, 10-30 g of butadiene (C) and 0.1-3 g of initiator (2) are added and the reaction is continued;

[0067] When the butadiene conversion rate (3) is 70-80%, 0.1-2 g of emulsifier (2) and 0.1-3 g of initiator (3) are added and the reaction is continued;

[0068] When the butadiene conversion rate (4) reaches ≥86%, the reaction is terminated by cooling to obtain a polybutadiene rubber latex.

[0069] Table 1 Examples 1-5 formulations and reaction conditions

[0070]

[0071]

[0072] Comparative Example 1

[0073] Preparation of polybutadiene rubber latex (a-1):

[0074] The process of Example 1 is repeated, except that all the materials added during the reaction of Example 1 are added into the reactor at once before the reaction starts, and then the reaction is carried out according to the reaction temperature of Example 1. After the conversion rate of Example 1 is reached, the temperature is lowered and the reaction is stopped to obtain polybutadiene rubber latex a-1.

[0075] Comparative Example 2

[0076] Preparation of polybutadiene rubber latex (a-2):

[0077] The process of Example 3 was repeated, except that the materials reaching butadiene conversion rate (1) and butadiene conversion rate (2) were combined together and added together when the butadiene conversion rate reached 25.5%. The subsequent operations were consistent with those of Example 3. When the final butadiene conversion rate reached 90.6%, the reaction was terminated by cooling to obtain polybutadiene rubber latex a-2.

[0078] Comparative Example 3

[0079] Preparation of polybutadiene rubber latex (a-3):

[0080] The process of Example 5 was repeated, except that the materials reaching butadiene conversion rate (2) and butadiene conversion rate (3) were combined together and added together when the butadiene conversion rate reached 57.0%. The subsequent operations were consistent with those of Example 5. When the final butadiene conversion rate reached 92.6%, the reaction was terminated by cooling to obtain polybutadiene rubber latex a-3.

[0081] The average particle size and particle size distribution index of the polybutadiene rubber latex prepared in Examples 1-5 and Comparative Examples 1-3, as well as the content ratio of particles larger than 800 nm, were tested. The results are shown in Table 2.

[0082] The average particle size, particle size distribution and proportion of particles larger than 800 nm of polybutadiene rubber latex were obtained by testing the diluted sample using a Malvern nanoparticle sizer (Zetasizer Nano series): 1 g of latex sample filtered through a 100-mesh filter was added to 100 g of deionized water for sufficient dilution, and then 1 g of the dilution was added to 100 g of deionized water for sufficient dilution, and then the average particle size, particle size distribution and proportion of particles larger than 800 nm of polybutadiene rubber latex were obtained by testing the diluted sample using a Malvern nanoparticle sizer (Zetasizer Nano series).

[0083] Particle size distribution and percentage of particles larger than 800 nm.

[0084] The test method of butadiene conversion rate is as follows: take 0.05g sample into a 20ml headspace bottle, dilute it to 1.00g with DMF, analyze the sample with a gas chromatograph, and test the residual butadiene monomer content. Substitute the test results into the following formula to calculate the butadiene conversion rate:

[0085]

[0086] Table 2 Test results of polybutadiene rubber latex prepared in Examples and Comparative Examples

[0087]

[0088] As shown in Table 2, according to the preparation examples 1-5 of the present invention, polybutadiene latex having an average particle size distribution of 260-300nm, a particle size distribution (PDI) ≤ 0.15, and a content of particles greater than or equal to 800nm ​​accounting for no more than 10wt% can be obtained, while the average particle size, particle size distribution and content of particles greater than or equal to 800nm ​​of the polybutadiene latex prepared as comparative examples 1-3 do not meet the index range required by the present invention.

[0089] Using the polybutadiene latex prepared in Examples 1-5 and Comparative Examples 1-3, MABS graft copolymer resins of Examples 6-10 and Comparative Examples 4-6 were prepared in the following manner.

[0090] Embodiment 6-10

[0091] According to the raw material types, amounts, and experimental conditions in Table 3, MABS graft copolymer resins (A-6 to 10) were prepared according to the following steps:

[0092] 25-50g of deionized water, 25-35g of alkyl acrylate monomer, 10-15g of styrene monomer and 1-10g of acrylonitrile monomer, as well as 0.001-0.1g of reducing agent, 0.01-1g of complexing agent, 0.01-1g of reducing agent, 0.5-5 of emulsifier (3), 0.1-3g of molecular weight control agent (2) and 0.01-0.3g of initiator (4) are continuously added to 50-70g of polybutadiene rubber latex prepared in step S1 to carry out graft polymerization of these monomers. The continuous feeding time is 3-6 hours. The temperature is controlled at 50-65°C during the continuous feeding. After the feeding is completed, the temperature is raised to 65-80°C and the aging is continued for 1-3 hours to obtain a MABS graft copolymer resin.

[0093] Table 3 Examples 6-10 formulations and reaction conditions

[0094]

[0095]

[0096] Comparative Example 4

[0097] Preparation of MABS graft copolymer resin a-4:

[0098] The process of Example 6 was repeated, except that the polybutadiene rubber latex A-1 prepared in Example 1 was replaced by the polybutadiene rubber latex a-1 prepared in Comparative Example 1 of equal mass, and other operations and conditions remained unchanged.

[0099] Comparative Example 5

[0100] Preparation of MABS graft copolymer resin a-5:

[0101] The process of Example 6 was repeated, except that the polybutadiene rubber latex A-1 prepared in Example 1 was replaced by the polybutadiene rubber latex a-2 prepared in Comparative Example 2 of equal mass, and other operations and conditions remained unchanged.

[0102] Comparative Example 6

[0103] Preparation of MABS graft copolymer resin a-6:

[0104] The process of Example 6 was repeated, except that the polybutadiene rubber latex A-1 prepared in Example 1 was replaced by the polybutadiene rubber latex a-3 prepared in Comparative Example 3 of equal mass, and other operations and conditions remained unchanged.

[0105] Add 2g H2SO4 and 200g deionized water into the coagulation kettle and start stirring to fully dissolve the H2SO4. Heat the coagulation kettle to 75°C and add 100g of the MABS graft copolymer resin latex prepared by Examples 6-10 and Comparative Examples 4-6 into the coagulation kettle in a continuous feeding manner for 1 hour. After the feeding is completed, heat the coagulation kettle to 90°C and keep it warm for 1 hour. Cool the coagulation kettle to room temperature and filter, wash and dehydrate the coagulation slurry to obtain ABS wet rubber powder. Dry the ABS wet rubber powder at 65°C in a fluidized bed dryer to a water content of <1% to obtain the MABS graft copolymer resin prepared by Examples 6-10 and Comparative Examples 4-6.

[0106] A twin-screw extruder was used at 200-220°C, with LG Chemical brand XT-500 MSAN resin as the blending continuous phase and the MABS graft copolymer resin prepared by Examples 6-10 and Comparative Examples 4-6 as the blending dispersed phase, and the blending, extrusion and granulation were performed according to a polybutadiene rubber content of 15% to obtain a thermoplastic transparent MABS resin.

[0107] The above MABS resin was used to prepare various test specimens at 190° C. on an injection molding machine. The light transmittance, haze and Izod notched impact strength of the thermoplastic transparent MABS resin were tested according to ASTM D1003 and ASTM D256, respectively. The results are shown in Table 3.

[0108] Table 3 Performance comparison of thermoplastic transparent MABS resin

[0109]

[0110] As can be seen from Table 3 above, unlike Comparative Examples 1-3, Examples 1-5 of the present invention obtain a transparent MABS resin composition with high transparency and impact resistance by controlling the mass proportion of large particles of polybutadiene rubber particles in the MABS graft copolymer resin and obtaining a specified rubber particle size and particle size distribution index. In addition, it can be seen that the light transmittance of the thermoplastic MABS resin prepared by Examples 1-5 is above 91.0, the haze value is below 1.8, and the cantilever beam impact strength is 16 kJ / m 2 above.

[0111] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. An acrylonitrile-butadiene-styrene-methyl methacrylate (MABS) graft copolymer resin, characterized in that: It is prepared from raw materials comprising the following parts by weight: 50-70 parts of polybutadiene rubber latex, 25-35 parts of alkyl acrylate monomer, 10-15 parts of styrene monomer, 1-10 parts of acrylonitrile monomer; The average particle size distribution of the polybutadiene rubber latex is 260-300 nm, the particle size distribution (PDI) is ≤0.15, and the content of particles with a diameter greater than or equal to 800 nm accounts for no more than 10 wt %.

2. The MABS graft copolymer resin according to claim 1, characterized in that: The alkyl acrylate monomer is one or more selected from methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, decyl (meth)acrylate and lauryl (meth)acrylate.

3. The MABS graft copolymer resin according to claim 1, characterized in that: The styrene monomer is one or more selected from styrene, α-methylstyrene, p-methylstyrene and vinyltoluene.

4. The MABS graft copolymer resin according to claim 1, characterized in that: The acrylonitrile monomer is one or more selected from acrylonitrile, methacrylonitrile and ethacrylonitrile.

5. The MABS graft copolymer resin according to claim 1, characterized in that: The polybutadiene rubber latex is butadiene homopolymer rubber latex.

6. A method for preparing the MABS graft copolymer resin according to any one of claims 1 to 5, characterized in that it comprises the following steps: S1: adding 70-110 parts by weight of deionized water, 1-5 parts by weight of electrolyte, 1-5 parts by weight of emulsifier (1), 0.1-3 parts by weight of molecular weight controller (1), 60-80 parts by weight of butadiene and 0.1-3 parts by weight of initiator (1) into a reactor, starting stirring and heating the reactor to 65-85° C.; When the butadiene conversion rate is 20-30%, 10-30 parts by mass of butadiene are added and the reaction is continued; When the butadiene conversion rate reaches 50-60%, 10-30 parts by weight of butadiene and 0.1-3 parts by weight of initiator (2) are added and the reaction is continued; When the butadiene conversion rate is 70-80%, 0.1-2 parts by weight of emulsifier (2) and 0.1-3 parts by weight of initiator (3) are added and the reaction is continued. When the butadiene conversion rate reaches ≥86%, the temperature is lowered to terminate the reaction, thereby obtaining a polybutadiene rubber latex. S2: 25-50 parts by weight of deionized water, 25-35 parts by weight of alkyl acrylate monomers, 10-15 parts by weight of styrene monomers and 1-10 parts by weight of acrylonitrile monomers, as well as 0.001-0.1 parts by weight of a reducing agent, 0.01-1 parts by weight of a complexing agent, 0.01-1 parts by weight of a reducing aid, 0.5-5 parts by weight of an emulsifier (3), 0.1-3 parts by weight of a molecular weight controller (2) and 0.01-0.3 parts by weight of an initiator (4) are continuously added to 50-70 parts by weight of the polybutadiene rubber latex prepared in step S1 to graft polymerize these monomers. The continuous feeding time is 3-6 hours. The temperature is controlled at 50-65° C. during the continuous feeding. After the feeding is completed, the temperature is raised to 65-80° C. and the aging is continued for 1-3 hours to obtain a MABS graft copolymer resin.

7. The preparation method according to claim 6, characterized in that: The emulsifiers (1), (2) and (3) are one or more selected from potassium oleate, potassium rosinate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium dodecyl allyl sulfosuccinate, dipotassium C16-C18 alkenyl succinate and dioctyl sodium sulfosuccinate; and / or The initiators (1), (2) and (3) are one or more water-soluble initiators selected from one or more of potassium persulfate, sodium persulfate, ammonium persulfate and hydrogen peroxide; and / or The initiator (4) is one or more oil-soluble initiators, selected from one or more of diisopropylbenzene hydroperoxide, tert-hexyl hydroperoxide, diisopropylbenzene peroxide, and tert-butylisopropylbenzene peroxide; and / or The electrolyte is one or more of potassium carbonate, sodium carbonate, potassium bicarbonate, sodium bicarbonate, sodium phosphate, sodium pyrophosphate, potassium pyrophosphate, and sodium tripolyphosphate; and / or The molecular weight control agents (1) and (2) are C8-C14 alkyl mercaptan, selected from one or more of tert-dodecyl mercaptan, n-dodecyl mercaptan, n-octyl mercaptan, primary octyl mercaptan, secondary octyl mercaptan, tert-octyl mercaptan and / or The reducing agent is one or both of ferrous sulfate and ferrous chloride; and / or The complexing agent is one or more of trisodium nitrilotriacetate, disodium ethylenediaminetetraacetate, tetrasodium ethylenediaminetetraacetate, sodium pyrophosphate, sodium hexametaphosphate, and / or The auxiliary reducing agent is one or more of sodium dithionite, sodium formaldehyde sulfoxylate, isoascorbic acid, glucose and lactose.

8. A transparent MABS resin composition, comprising the MABS graft copolymer resin according to any one of claims 1 to 5 or the MABS graft copolymer resin prepared by the method according to claim 6 or 7 and methyl methacrylate-styrene-acrylonitrile (MSAN) resin; The content of the MABS graft copolymer resin in the transparent MABS resin composition is 15-30wt%, preferably 15-25wt%, more preferably 20-25wt%.

9. The transparent MABS resin composition according to claim 8, wherein: The MSAN resin is a resin prepared by polymerizing 0-75 parts by weight of a (meth)acrylic acid alkyl ester monomer, 10-50 parts by weight of a styrene monomer, and 10-20 parts by weight of an acrylonitrile monomer.

10. A thermoplastic transparent MABS resin, characterized in that: Prepared by extrusion and injection molding of the transparent MABS resin composition according to claim 8 or 9; Preferably, the thermoplastic MABS resin has a light transmittance of 91.0 or more and a haze value of 1.8 or less measured on a 3 mm thick sheet at room temperature according to ASTM D1003; and an Izod impact strength of 16 kJ / m 2 above.

Citation Information

Patent Citations

  • Transparent copolymer resin, method for preparing the transparent copolymer resin, and resin blend composition including the transparent copolymer resin

    CN101072803B

  • Thermoplastic resin composition with excellent transparency, improved impact strenght and reduced cold stress whitening

    CN103180383A

  • Transparent ABS resin and transparent ABS resin composition

    CN105008406A

  • High-flowability transparent ABS resin with pomegranate structure and preparation method thereof

    CN116063805A